Identifying Determinants of Concurrent Anemia and Stunting Among Young Children - Margawati, Ani; Purwanti, Rachma; Ahmad Syauqy; Fadhila, Farah Rosyihana (Universitas Airlangga, 2026)
Stunting and anemia are prevalent nutritional problems that often concurrently occur in young children, particularly in developing countries such as Indonesia. The coexistence of these conditions can have long-lasting adverse effect on a child’s health, cognitive development, and future productivity. This study aimed to investigate the determinants of concurrent anemia and stunting in children aged 6–36 months in Semarang City. A cross-sectional study design was employed from June to September 2024, involving 100 stunted children selected using purposive sampling. Data were collected through structured interviews using questionnaires, anthropometric measurements, hemoglobin testing, and observations of caregiving practices. Bivariate and multivariate logistic regression analyses were conducted to identify factors associated with the occurrence of concurrent anemia and stunting. Several factors were found to be significantly associated with concurrent anemia and stunting, including birth length <48 cm (OR = 6.190; p = 0.027), incomplete immunization history (OR = 16.024; p = 0.035), preterm birth (OR = 6.539; p = 0.015), poor maternal attitudes toward feeding practices (OR = 33.459; p = 0.018), and inappropriate complementary feeding practices (OR = 7.889; p = 0.007). A paternal history of smoking also showed a tendency to be a risk factor (p = 0.080). The co-occurrence of anemia and stunting is a complex issue influenced by a multitude of factors, including biological, behavioral, and household or environmental determinants. To effectively address this issue, integrated interventions should be implemented, focusing on enhancing immunization coverage, providing targeted nutrition education, strengthening antenatal care, and promoting positive caregiving practices.